FORMAT BARU DEWAN PERWAKILAN RAKYAT PASCA AMANDEMEN UUD 1945 - Lili Romli (Jurnal Politica, 2012)
The amendments of the 1945 constitution have given stronger authority to DPR in making law, conducting its oversight function over executive body, and demonstrating its authority in selecting public officials. The current political situation is, therefore, legislative heavy in nature. This essay focuses on stronger role of DPR after the amendments. Importantly, the change of heavy in the legislative function from executive to legislative, especially in making oversight function, and the sorts of the strengthening role, becomes the main interest of the writer.